2007
DOI: 10.1007/s00540-006-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control for anesthesiologists

Abstract: Anesthesiologists daily witness the consequences of tobacco use, the most common preventable cause of death. Smoking-related diseases such as atherosclerosis and chronic obstructive pulmonary disease increase anesthetic risk, and even smokers without overt disease are at increased risk for morbidity such as pulmonary and wound-related complications. Evidence suggests that stopping smoking will reduce the frequency of these complications. Nicotine and the other constituents of cigarette smoke, such as carbon mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 167 publications
0
11
0
Order By: Relevance
“…However, based on data from cigarette smoking patients regarding COHb and nicotine levels, refraining from waterpipe use for at least 12 hours (about three COHb elimination half-lives) before elective surgery, as is often recommended for cigarette smokers, is probably desirable [7,9,20]. Since COHb may reach levels markedly higher in waterpipe users than in cigarette users, this recommendation is likely even more important [12].…”
Section: Discussionmentioning
confidence: 95%
“…However, based on data from cigarette smoking patients regarding COHb and nicotine levels, refraining from waterpipe use for at least 12 hours (about three COHb elimination half-lives) before elective surgery, as is often recommended for cigarette smokers, is probably desirable [7,9,20]. Since COHb may reach levels markedly higher in waterpipe users than in cigarette users, this recommendation is likely even more important [12].…”
Section: Discussionmentioning
confidence: 95%
“…Many studies suggest determination of COHb in clinical practice [20] . The risk of anesthesia and the incidence of postoperative respiratory complications are increased in smoking population [21] . It has been reported that COHb is produced by the interaction of volatile anesthetics, including sevo¬flurane [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified numerous barriers to staff delivery of cessation advice [21,22] . In our view, anesthetic personnel may not fully appreciate the risks of smoking in the immediate perioperative period.…”
Section: Discussionmentioning
confidence: 99%